Meta‑analysis of conjugated linoleic acid use in pigs feeding - Andretta, Ines; Lovatto, Paulo Alberto; Lehnen, Cheila Roberta; Hauschild, Luciano; Rossi, Carlos Augusto Rigon (Pesquisa Agropecuaria Brasileira, 2010)
This work aimed at meta-analyzing the association of conjugated linoleic acid (CLA) with the performance and the carcass and meat quality in pigs (Sus scrofa domesticus). The database used assembled 15 scientific papers, published from 1999 to 2006, comprising 216 diets and 5,223 animals. Meta-analysis was carried out by graphical examination (to observe biological coherency), correlation (to identify correlated variables) and variance-covariance analysis of the data. The analysis of variance included only meat and carcass variables with stronger correlation to CLA consumption by the animals, and encodings to inter and intra-experimental effects. The inclusion of CLA in diets showed a negative correlation with feed efficiency and a positive correlation with feed intake and weight gain. Conjugated linoleic acid-suplemented diets for pigs did not affect feed intake, weight gain and feed efficiency. Conjugated linoleic acid increased the lean meat content in the carcass in 9%. Average backfat thickness also varied according to conjugated linoleic acid consumption. Conjugated linoleic acid increases lean meat content and reduces backfat thickness, without influencing performance and meat quality in pigs.